Pengaruh Kepemimpinan Motivasi Kerja Dan Pengendalian Internal Terhadap Kinerja Pegawai Satpol Pp Kabupaten Demak - Hadi, Syamsul; Supriyadi, Andhi; Yuliamir, Henry (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2024)
The purpose of this study, which was carried out at the Satpol PP Demak Regency, was to ascertain how internal control, motivation, and leadership affected staff performance. Quantitative research methodologies were used for this study. 82 Satpol PP employees made up the sample. Multiple linear regression was performed and used using SPSS to evaluate the data collected through surveys. Regression analysis' findings demonstrate that leadership has a significant impact on worker performance. Since leadership has a greater impact on employee performance than work motivation and internal control, Satpol PP employees require strong leadership from their supervisors. While internal controls, motivation, and leadership all influence how well employee work.